THE RELATIONSHIP BETWEEN SOCIO-ECONOMIC, EATING PATTERNS AND EXCLUSIVE BREASTFEEDING WITH UNDERNUTRITION IN TODDLERS IN MERAK VILLAGE - Caesaria, Fairuz Hasna; Mufidah, Indahtul; Siswiyanti, Ikha; Pibriyanti, Kartika; Luthfiyah, Lulu' (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Various factors such as socioeconomic conditions, dietary patterns, and exclusive breastfeeding practices contribute to the incidence of undernutrition among toddlers. A preliminary study in Merak Village recorded that approximately 21.5% of toddlers were affected by undernutrition. This study aims to explore the association between socioeconomic status, dietary patterns, and exclusive breastfeeding practices with the incidence of undernutrition among toddlers in Merak Village. A case-control design was employed, involving 50 respondents in each group, selected through purposive sampling. The sample size was determined using the Lemeshow formula. Undernutrition served as the dependent variable and was assessed based on the weight-for-age (W/A) index. sosioeconomi and exclusive breastfeeding variables using questionnaires and eating pattern using SQ-FFQ questionnaires. The data were statistically analyzed through the chi-square test and multivariate logistic regression model. The findings demonstrated significant associations between undernutrition and several variables, including family income (p = 0.012; OR = 0.316), meal frequency (p < 0.001; OR = 11.156), quantity of food intake (p < 0.001; OR = 24.571), and exclusive breastfeeding (p < 0.001; OR = 0.141). In contrast, maternal education (p = 0.288; OR = 0.566), paternal occupation (p = 0.691; OR = 1.000), and maternal occupation (p = 0.161; OR = 1.909) did not exhibit statistically significant relationships with undernutrition. Multivariate analysis further revealed that meal frequency, the amount of food intake, and exclusive breastfeeding were influential determinants of undernutrition among toddlers. Among these, exclusive breastfeeding emerged as the most dominant factor. Overall, family income, dietary practices, and breastfeeding status were identified as key risk factors contributing to undernutrition in early childhood.